From the narrow to the broad. Multiple perspectives on language evolution - Wacewicz, Sławomir; Żywiczyński, Przemysław (Theoria et Historia Scientiarum, 2015)
Although many of the recent controversies in the field of language evolution research are empirical, the deepest divides seem to remain theoretical in nature. Specifically, defining language in incompatible ways has led to radically different views on language evolution as a programme, including evaluation of its current success and future progress. Despite recent manifestos from the “narrow” camp (Hauser et al. 2014; Bolhuis et al. 2014), who along the lines of Hauser, Chomsky and Fitch (2002) equates language with the syntactic processor, the rival approach seems to be gaining momentum. It embodies a move in exactly the opposite direction, by understanding language broadly and assuming an inclusive perspective on its origins, which results in ongoing expansion of the field of language evolution. New areas of academic reflection (such as normativity) are being brought to bear, new areas of linguistics are being included (such as pragmatics or linguistic politeness); and, interestingly, existing linguistic methods are now being used to inform animal communication studies.